Concerns and nutritional needs after natural disasters - azadeh najarzadeh; adel eftekhari; javad sadat; maryam azizi; samaneh mirzaei (فصلنامه ابن سینا)
Background: One of the most important tasks of community leaders is to anticipate, plan, and provide the necessary measures deal with the crisis and its consequences. Providing safe as well as healthy water and food for those affected is one of the most important steps that governments should take. The present article reviewed nutritional needs at the time of natural disaster and measures needed to address them. Materials and methods: In this review study, data were collected using databases searching and keywords nutrition, management, crisis, disasters, and rations from 1960 to 2017. Results: After reviewing the studies, it was observed that after the disasters, firstly, measures such as population estimation for service provision, probable estimation of infant children, climatic conditions of the region, food-aware human resources and etc., should be done by food management in times of crisis. After evaluating the nutritional status of the priority groups, it should be designed to each individual nutrition management plan. Conclusion: Due to the important role of nutrition in disasters, the best nutritional content should be provided in accordance with the conditions of disasters, available standards for any type of foodstuff and appropriate for any age, sex, etc., should be provided, and according to nutritional requirements and inaccessibility of foodstuffs, powder packages with needed ingredients for rapid dissolution in water should be prepared.